Pengaruh Senioritas, Prestasi Kerja, Dan Motivasi Kerja Terhadap Produktivitas Karyawan Di Indomaret Sumedang 2 Kepanjen - Alfrian Nidal; Abdul Kodir Djaelani; Mohammad Rizal (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This study aims to examine the effect of seniority, work performance, and work motivation on employee productivity at Indomaret Sumedang 2 Kepanjen. The population in this study is all employees at Indomaret Sumedang 2 Kepanjen. The number of samples used is the same as the population or called a census, namely 32 people. The analytical method used is multiple linear regression analysis using the IBM SPSS 25 (Statistical Product and Service Solutions) application tool. Based on testing using the simultaneous F test analysis, the results showed that there was a significant influence between the X variable (Seniority, Work Achievement, and Work Motivation) simultaneously on the Y variable (employee productivity) at Indomaret Sumedang 2 Kepanjen and the partial test analysis (t test) in Research shows that the seniority variable has a positive and significant effect on the productivity of Indomaret Sumedang 2 Kepanjen, work performance has a positive and significant effect on the productivity of Indomaret Sumedang 2 Kepanjen, work motivation has a positive and significant effect on the productivity of Indomaret Sumedang 2 Kepanjen. Keywords: Seniority, Work Performance, Work Motivation, Employee Productivity